A case report of congenital high airway obstruction syndrome (CHAOS) caused by complete laryngeal obstruction - Rahman, T; Khalequezzaman, S; Ahsan, S; Alam, J; Sarker, MK (Pulse, 2015)
CHAOS or Congenital High Airway Obstruction Syndrome is a blockage of the fetuss trachea or larynx due to a number of factors including narrowing of the airway, a web-like membrane or even tracheal atresia. In the uterus, the fetal lungs constantly produce fluid and as a result of this airway blockage in the trachea, the lung fluid cannot escape out of the fetal mouth. Because of this the fetuss lungs become distended with fluid and over distended lungs can put pressure on the heart and affect the hearts ability to function. If the heart cannot beat effectively hydrops or congestive heart failure can occur. We present a case of CHAOS with hydrops and associated anomalies, determined prenatally at about 21 weeks by MRI in our hospital. Pulse Vol.7 January-December 2014 p.38-41